2019
DOI: 10.1039/c9tb00837c
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun PCL/Gel-aligned scaffolds enhance the biomechanical strength in tendon repair

Abstract: The PCL/Gel-aligned scaffolds could enable to improve the regenerated tendon tissue with highly aligned cells and good mechanical strength in a rabbit patellar tendons injured model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 47 publications
2
35
0
Order By: Relevance
“…The samples were cut into 10 × 90 mm and were tested in triplicates, Figure 2. Similar testing conditions were reported elsewhere [44]. coating, at different magnifications.…”
Section: Tensile Testingsupporting
confidence: 57%
“…The samples were cut into 10 × 90 mm and were tested in triplicates, Figure 2. Similar testing conditions were reported elsewhere [44]. coating, at different magnifications.…”
Section: Tensile Testingsupporting
confidence: 57%
“…Electrospinning, the fleece fabrication technology used in this research, is relatively economical, controllable, reproducible, and suitable and has encouraged researchers to use it in tissue engineering, especially for in vivo studies [46,47]. Even if natural substances such as collagen and fibrin [48] are more biocompatible, many synthetic polymers have been used in tendon tissue engineering such as PCL [14,49], PLLA [47,50], chitosan [51], a mixture of polymer PLLA/PCL [52], PCL/Gel [53,54], and PLGA, which has been widely used in tendon tissue engineering [16,40,[55][56][57]. This material has been chosen to fabricate the fleece used in this work since it is FDA-approved and provides sufficient control of degradation [58,59] combined with a sufficient mechanical strength that fosters its application for tissue remodeling and regeneration [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…Fibers generated from synthetic polymers have been shown to strengthen the overall scaffold, while the naturally-derived fibers maintain their cell biocompatibility [30]. In other studies, scaffold strength was improved by electrospinning substrates with aligned fibers [31,32]. Moffat et al reported that aligned poly (lacticco-glycolic acid) (PLGA) electrospun fibers exhibited a 3-fold increase in the yield strength compared with unaligned fibers [31].…”
Section: Discussionmentioning
confidence: 99%